PWE-045 A Strong Correlation Exists between Morphologic and Genomic Heterogeneity in Hepatocellular Carcinoma (HCC). (17th August 2016) - Fateen, W; Wood, H; Berri, S; Thygesen, H; Wyatt, J; El- Meteini, M; Millson, C; Quirke, P
Abstract : Introduction: Morphological intra-tumour heterogeneity is well recognised in HCC. Genomic intra-tumour heterogeneity has recently been reported on a small number of cases. In this study we aim to correlate morphological and genomic heterogeneity in HCV related HCC to inform the need for multiple biopsies Methods: We investigated DNA copy number profiles of 12 HCV induced nodules with morphological heterogeneity and 8 morphologically homogeneous nodules. Histologically homogenous nodules (n = 8) were sequenced at 29 areas. 5/8 nodules were divided into 4 equal quadrants and DNA was extracted from each of the quadrants. The remaining 3/8 nodules were embedded into several paraffin blocks (range 2–5) upon routine processing post operatively. One DNA sample was extracted from each paraffin block All grades of differentiation were included as well as dysplastic nodules. A total of 35 correlations were performed between DNA sequences from different areas in this group. Morphologically heterogeneous nodules (n = 12) were sampled from morphologically distinct areas showing variability in either differentiation, cytological or morphological patterns within the same tumour. A total of 16 correlations were performed from different areas in this group. Differences in copy number patterns were objectively analysed using Pearson's correlation between normalised, non- smoothed, non-segmented ratios (n = 27, 180 per each sample). Results: Pearson's correlation coefficients were consistently >0.85 (mean = 0.92 after Fisher r to z to r transformation) indicating a strong positive linear correlation between the studied sequences in the morphologically homogenous group. Marked genomic heterogeneity existed in morphologically heterogenous samples. Mean correlation coefficient was 0.62 for tumours that were exclusively HCC (n = 7) and and 0.48 for tumours where an area of dysplasia was engulfed within the nodule (n = 5) respectively.The difference between correlations coefficients of morphological homogenous versus heterogenous groups was statistically significant (P = 0.01). Conclusion: We therefore confirm the presence of intra-tumour heterogeneity in a number of HCV related HCC. However, we only identified intra-tumour heterogeneity in morphologically heterogeneous samples but not in those that harbour uniform morphology. Confirmation that morphologically homogenous samples are genetically homogenous is highly relevant clinically especially with rising doubts about the role of liver biopsy in HCC. Disclosure of Interest: W. Fateen: None Declared, H. Wood: None Declared, S. Berri Employee of: Illumina, H. Thygesen: None Declared, J. Wyatt: None Declared, M. El- Meteini: None Declared, C. Millson: None Declared, P. Quirke: None Declared